Changes in prenatal testing during the COVID-19 pandemic - Handley, Sara C.; Ledyard, Rachel; Lundsberg, Lisbet S.; Passarella, Molly; Yang, Nancy; Son, Moeun; McKenney, Kathryn; Greenspan, Jay; Dysart, Kevin; Culhane, Jennifer F.; Burris, Heather H. (Frontiers in Pediatrics, 2022)
Objective: The coronavirus disease 2019 (COVID-19) pandemic disrupted healthcare delivery, including prenatal care. The study objective was to assess if timing of routine prenatal testing changed during the COVID-19 pandemic. Methods: Retrospective observational cohort study using claims data from a regional insurer (Highmark) and electronic health record data from two academic health systems (Penn Medicine and Yale New Haven) to compare prenatal testing timing in the pre-pandemic (03/10/2018-12/31/2018 and 03/10/2019-12/31/2019) and early COVID-19 pandemic (03/10/2020-12/31/2020) periods. Primary outcomes were second trimester fetal anatomy ultrasounds and gestational diabetes (GDM) testing. A secondary analysis examined first trimester ultrasounds. Results: The three datasets included 31,474 pregnant patients. Mean gestational age for second trimester anatomy ultrasounds increased from the pre-pandemic to COVID-19 period (Highmark 19.4 vs. 19.6 weeks; Penn: 20.1 vs. 20.4 weeks; Yale: 18.8 vs. 19.2 weeks, all p<0.001). There was a detectable decrease in the proportion of patients who completed the anatomy survey <20 weeks’ gestation across datasets, which did not persist at <23 weeks’ gestation. There were no consistent changes in timing of GDM screening. There were significant reductions in the proportion of patients with first trimester ultrasounds in the academic institutions (Penn: 57.7% vs. 40.6% and Yale: 78.7% vs. 65.5%, both p <0.001) but not Highmark. Findings were similar with multivariable adjustment. Conclusion: While some prenatal testing happened later in pregnancy during the pandemic, pregnant patients continued to receive appropriately timed testing. Despite disruptions in care delivery, prenatal screening remained a priority for patients and providers during the COVID-19 pandemic.